Impact of a large deletion in the neuraminidase protein identified in a laninamivir‐selected influenza A/Brisbane/10/2007 (H3N2) variant on viral fitness in vitro and in ferrets. Issue 2 (29th January 2016) - Ann, Julie; Abed, Yacine; Beaulieu, Edith; Bouhy, Xavier; Joly, Marie‐Hélène; Dubé, Karen; Carbonneau, Julie; Hamelin, Marie‐Eve; Mallett, Corey; Boivin, Guy
Abstract : Viral fitness of a laninamivir‐selected influenza A/Brisbane/10/2007‐like (H3N2) isolate (LRVp9) containing a 237‐amino acid neuraminidase deletion and a P194L hemagglutinin mutation was evaluated in vitro and in ferrets. LRVp9 and the wild‐type (WT) virus showed comparable replication kinetics in MDCK‐ST6GalI cells. Cultured virus was recovered between days 2 and 5 post‐infection in nasal washes (NW) from the 4 WT‐infected ferrets whereas no virus was recovered from the LRVp9‐infected animals. There was a ≥1 log reduction in viral RNA copies/μl of NW for LRVp9 compared to WT at most time points. The large neuraminidase deletion compromises viral infectivity in vivo .